CARBON AND OXYGEN ISOTOPIC COMPOSITIONS OF CARBONATES FROM PRECAMBRIAN APATITE-BEARING CARBONATE ROCKS OF THE ALDAN SHIELD - Guliy V.N.; Wada H. (My University, 2004)
Geostructural setting, as well as mineral and isotopic compositions, of separate apatite deposits and occurrences in the Aldan Shield composed of Precambrian metasedimentary apatite–carbonate rocks are considered. In terms of carbon and oxygen isotopic compositions, they differ from other carbonate rocks of the Aldan Shield, including carbonatites and Ca–Mg metasomatites, and resemble Phanerozoic and Precambrian metasedimentary carbonates. They formed in oxidizing conditions. The contribution of evaporite processes at different stages of their formation is supported by the carbonate enrichment in 13C and the presence of sulfates. It was established that apatite–carbonate rocks represent the product of complex alternation of sedimentary processes at different values of salinity in the basins occasionally characterized by the decomposition of older sediments under subaerial conditions.
Keywords: Aldan Shield; apatite; Precambrian; Докембрий